2011
DOI: 10.1002/aoc.1751
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and microwave‐assisted catalytic activity of novel benzimidazole salts bearing piperidine and morpholine moieties in Heck cross‐coupling reactions

Abstract: A mixture of novel benzimidazole salts (2a-f), Pd(OAc) 2 and K 2 CO 3 in DMF-H 2 O catalyzes, in high yield, the Heck crosscoupling reaction assisted by microwave irradiation in a short time. All synthesized novel benzimidazole derivatives were characterized by elemental analysis and NMR spectroscopy. In addition, the molecular structure of 2a was determined by X-ray crystallography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 50 publications
3
13
0
Order By: Relevance
“…For the benzimidazolium salts 2a – c , it was found to be 142.5, 142.8, and 142.2 ppm, respectively. These values are in good agreement with the previously reported results .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…For the benzimidazolium salts 2a – c , it was found to be 142.5, 142.8, and 142.2 ppm, respectively. These values are in good agreement with the previously reported results .…”
Section: Resultssupporting
confidence: 93%
“…The compounds ( 1a–c and 2a–c ) show IR absorption bands at wavelengths and that vary from 1550 to 1658 cm −1 , which are assigned to ν (CN). These IR absorption values are in good agreement with previously reported values for NHC salts .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The catalytic yield of the coupling is dependent on a variety of parameters such as temperature, solvent, base and nature of catalyst loading. We recently reported the optimum reaction conditions for the Suzuki/Heck coupling reaction, including some benzimidazolium or bis‐benzimidazolium saltsPd(OAc) 2 and base as a catalyst system under microwave and conventional heating conditions 27, 53, 54. In the present report, a series of aryl chloride and aryl bromide were used for coupling partner with phenylboronic acid.…”
Section: Resultsmentioning
confidence: 95%
“…[22,23] In our previous studies, we used several in situ prepared palladium-N-heterocyclic carbenes derived from benzimidazole for the Suzuki, Heck and Buchwald-Hartwig reactions under microwave irradiation conditions and obtained promising catalytic results. [24][25][26][27][28][29][30] The use of a metal catalyst as nanoparticles generally accelerates the catalytic conversion and the use of nanoparticles in cross-coupling reactions has attracted a great deal of interest because of their effectiveness. Therefore, several studies have been reported relating to the use of palladium nanoparticles in cross-coupling reactions.…”
Section: Introductionmentioning
confidence: 99%